Development of a Simple Seismograph Tool as a Media for Learning Social Science Material in Elementary Schools - Nur Alawiyah; Tuti Istianti; Muh. Husen Arifin (Institut Pendidikan Indonesia, 2021)
Learning media is an important component in the world of education. In its use, learning media is used to explain and convey information related to the learning being carried out. Learning media helps teachers to attract students' attention when learning. The aim of this research is to determine the effect of developing simple seismograph learning media on material regarding the impact of Indonesia's geographic location in elementary schools. Social studies learning in elementary schools needs to be reformed so that when presenting the material we don't just use the lecture method which results in making students bored and disengaged when learning. Therefore, the researcher created this research so that teachers can always develop something new, namely by developing learning media in the form of a seismograph that is simply designed. This research uses a descriptive method. The results of the research can be concluded that by developing a simple seismograph tool as a learning medium for social studies material in elementary schools about the impact of Indonesia's geographic location on the material samples taken, namely earthquakes. It can be stated that using and making this simple seismograph tool is able to make students involved in learning, make students' curiosity high when studying and can motivate students to learn actively. Its simple production is an added value in the development of this learning media because it is suitable for use by elementary school children.